Work From Anywhere (WFA): Formulation of Policy Design for the Work System of State Civil Apparatus as Government Bureaucratic Efficiency In The New Normal Era - Daffa Ladro Kusworo; Maghfira Nur Khaliza Fauzi (Fakultas Hukum Universitas Lampung, 2022)
The changes in the order of people's lives after the Covid-19 pandemic stimulated the government to find the right policy direction, especially related to the work system of the State Civil Apparatus (ASN). Efforts to build a more adaptive work mechanism in dealing with crises initially created a Flexible Working Arrangement (FWA) policy which was implemented with Work From Home (WFH) as stated in the KemenPANRB Circular Number 19 of 2020 concerning Adjustment of the ASN System in Efforts to Prevent the Spread of Covid-19 The implementation of this policy has succeeded in achieving performance so that in the long term the government plans to implement a new work system model in the current New Normal era, namely Work From Anywhere (WFA). Later, ASN can work according to their convenience to improve the performance and better quality of public services. This formulation is also the embodiment of Industry 5.0 in work culture, so instead of closing oneself off from a restrictive system and working time, people can align it with the ever-evolving technology infrastructure as part of the reform agenda set out in Presidential Regulation No. 81 2010. This study uses a normative legal research method with an approach to legislation and literature study and uses descriptive analysis in managing qualitative data by applying a deductive method. The study results explain that the WFA concept is a new step for the government with a monitoring and evaluation system for ASN Number 8 of 2022. Furthermore, it is recommended to form a PermenPANRB. It is hoped that it will not only be a temporary solution but future-oriented in improving the performance of ASN based on the actual result.